Effect of Nano Materials on Geotechnical Properties of Expansive Soils: A Review (Diyala Journal of Engineering Sciences, 2025)
Expansive soils are responsible for extensive infrastructure damage worldwide, prompting the urgent search for innovative, sustainable stabilization methods. Nanomaterials have emerged as a promising next-generation solution capable of addressing both performance and environmental challenges. This review investigated the use of nanomaterials such as nano-silica, nano-alumina, nano-copper, nano-MgO, and nano-calcined clay and terrasil, and a combination of nanomaterials with lime or cement (hybrid) as sustainable stabilizers. It was found that plasticity index (PI) decreases by 20-60%, optimum moisture content decreases of 10-12%, and maximum dry density increases of 5-10% for ≤1% nonadditive. Swell potential and swell pressure typically reduced by 20-30% or more at dosages ≤1-1.5%, while hybrid mixes achieve even higher reductions. Strength gains were particularly significant: unconfined compressive strength (UCS) commonly doubles in the short term and exceeds 5 times untreated values with long-term curing, reaching up to 6 times with hybrid stabilization. Similarly, soaked CBR values improve by about 2 times with nanomaterials alone and up to 5-6 times with hybrid systems. These mechanical enhancements were supported by microstructural evidence showing pore filling, formation of cementitious gels (CSH, CAH, MSH, CASH), and surface coatings that densify soil, strengthen particle bonding, and reduce water ingress. Performance was strongly dosage- and material-dependent, with excessive amounts sometimes leading to agglomeration and reduced efficiency. Overall, findings confirmed that nanomaterials, especially when combined with lime or cement, provided a reliable, sustainable, and long-term stabilization approach, offering substantial improvements in expansive soil behavior and geotechnical infrastructure performance.